2020
DOI: 10.2147/ijn.s270311
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhanced Osseointegration of Titanium Implants by Surface Modification with Silicon-doped Titania Nanotubes</p>

Abstract: Introduction Despite great progress made in developing orthopedic implants, the development of titanium (Ti) implants with ideal early osseointegration remains a big challenge. Our pilot study has demonstrated that Si-TiO 2 nanotubes on the surface of Ti substrates could enhance their osteogenic activity. Hence, in this study, we aim to comprehensively evaluate the effects of silicon-doped titania (Si-TiO 2 ) nanotubes on the osseointegration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…From the perspective of molecular biology of osteoblasts, osteoclasts, fibroblasts, and mesenchymal stem cells, the mechanisms of bone aggregation, osteoinduction, and osseointegration on titanium implants have been deeply studied [ 116 , 117 , 118 , 119 ]. However, in recent years, there have been more and more explorations of the role of integrins on the surface of bone cells.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of molecular biology of osteoblasts, osteoclasts, fibroblasts, and mesenchymal stem cells, the mechanisms of bone aggregation, osteoinduction, and osseointegration on titanium implants have been deeply studied [ 116 , 117 , 118 , 119 ]. However, in recent years, there have been more and more explorations of the role of integrins on the surface of bone cells.…”
Section: Discussionmentioning
confidence: 99%
“…The energy of the injected ions is gradually lost and the ions stay within the implant, causing changes in its surface composition, structure, and performance. Zhao et al 65 Runx2), calcium deposition, and implant-tissue interface bonding strength.…”
Section: Plasma Immersion Ion Implantation (Piii)mentioning
confidence: 99%
“…Si, another bioactive trace element, possesses a bone affinity that has been shown to enhance osteoblast proliferation and differentiation, stimulate collagen synthesis and bone mineralization [ 292 , 293 ], and to further inhibit the osteoclastogenesis and bone resorption processes [ 294 ]. Zhao et al [ 277 ] fabricated Ti substrates (discs and screws) modified with silicon doped TiO 2 NTs (Si-TiO 2 -NTs) by in situ anodization and Si plasma immersion ion implantation (PIII) technique and compared their activities with those for Ti and TiO 2 NTs. The in vivo results, in line with the in vitro findings, showed that the Si-TiO 2 -NTs surface increased pre-osteoblast cell proliferation and differentiation, indicated extensive bone apposition between the screw threads at the spongy level on this surface and the formation of more new trabecular bone as compared to bare Ti and TiO 2 -NTs screws.…”
Section: Tailoring Osteoinduction With Anodic Tio 2 Nanotubesmentioning
confidence: 99%